Catalyst for preparing alpha-diisobutylene by oligomerization of isobutylene and preparation method of catalyst
By combining nitrates of copper, cobalt or nickel with Beta molecular sieve, a catalyst for isobutene oligomerization reaction was prepared, which solved the problem of poor selectivity of α-diisobutene in existing catalysts, and achieved the effect of efficient preparation of isononanal raw materials.
Patent Information
- Application Number
- CN202411824694.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-11
AI Technical Summary
The selectivity of α-diisobutene in the isobutene oligomerization reaction of existing catalysts is poor, making it difficult to meet the efficient preparation needs of isononanal raw materials.
The catalyst is prepared by combining nitrates of copper, cobalt or nickel with Beta molecular sieve and through impregnation, ultrasonication, stirring, drying and calcination, etc., for isobutene oligomerization reaction.
The selectivity of α-diisobutylene is improved, the conversion rate of isobutylene is above 50%, and the proportion of α-diisobutylene in dimer is as high as more than 90%, meeting the efficient preparation needs of isononanal raw materials.
Smart Images

Figure CN119588409A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and particularly relates to a catalyst for preparing alpha-diisobutylene through isobutylene oligomerization and a preparation method thereof. Background Art
[0002] Mixed carbon, as a by-product of catalytic cracking and steam cracking in the process of petroleum refining, is a very important chemical resource. It contains a large amount of usable high-carbon olefins, especially C8-C12 high-carbon α-olefins, which can be used to produce polyalphaolefins (PAO) and further synthesize high-end lubricants with high added value.
[0003] As a key raw material for high-end lubricants or an additive for lubricants, isononanoic acid has good lubrication performance and thermal stability. At present, there are three main process routes for the preparation of isononanoic acid at home and abroad: (1) using isooleic acid as the raw material, and obtaining the product through oxidative decomposition reaction; (2) using olefins as the raw material, and obtaining isononanal through hydroformylation reaction under the action of catalyst, and then obtaining the product through oxidation reaction; (3) using isononanol as the raw material, and obtaining the product through oxidation reaction. Among them, the second process route is the most mainstream isononanoic acid production method at this stage. α-Diisobutylene (2,4,4-trimethyl-1-pentene) in C8 olefins is one of the raw materials for synthesizing isononanal, which can be obtained through isobutylene polymerization reaction. However, in the process of isobutylene polymerization, the product is complex and the selectivity of α-diisobutylene is very poor, which has become an urgent problem to be solved in the process of synthesizing isononanal.
[0004] Isobutylene polymerization is a typical acid-catalyzed reaction process, and the catalysts mainly include liquid acid catalysts and solid acid catalysts. When liquid acid catalysts such as sulfuric acid and toluenesulfonic acid were used in the early stage, the reaction selectivity was poor, the purity of the product isobutylene dimer was very low, the catalyst was difficult to separate and it was corrosive to the production equipment, which made it difficult to meet the actual production needs. At present, solid acid catalysts have gradually become a hot topic of research, mainly including solid phosphoric acid catalysts, oxides and composite oxide catalysts, ion exchange resin catalysts, molecular sieve catalysts, etc.
[0005] Although solid phosphoric acid catalysts have a long history of application in olefin polymerization, their application has gradually decreased due to problems such as poor water resistance and low mechanical properties; oxide composite oxide catalysts and ion exchange resin catalysts are both due to their strong surface acidity. Although they show high reactivity in the isobutylene polymerization process, trimers and tetramers are more likely to be generated in the product, and the alpha olefin selectivity in the product is poor. Therefore, it is imperative to develop a cheap and efficient catalyst for the synthesis of alpha-diisobutylene, the raw material of isononanal. Summary of the invention
[0006] Aiming at the problem of poor selectivity of α-diisobutylene in existing catalysts, the present invention provides a catalyst for preparing α-diisobutylene by isobutylene oligomerization and a preparation method thereof. The preparation process is simple, the reaction process conditions are mild, the selectivity of α-diisobutylene in the product is high, the isobutylene conversion rate is above 50%, the total selectivity of α-diisobutylene is greater than 50%, and its proportion in dimer is as high as above 90%.
[0007] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a catalyst for preparing alpha-diisobutylene by isobutylene polymerization, characterized in that copper, cobalt or nickel nitrate is dissolved in deionized water, a carrier Beta molecular sieve is added, equal volumes are impregnated, ultrasonicated, stirred, dried at 70-100°C, and then heated to 300-600°C in a muffle furnace and calcined for 2-5h to obtain the catalyst for isobutylene polymerization.
[0008] The nitrate of copper, cobalt or nickel is one or more of copper nitrate trihydrate, cobalt nitrate hexahydrate and nickel nitrate hexahydrate.
[0009] The mass ratio of the copper, cobalt or nickel nitrate to the Beta molecular sieve is 1:5-1:40.
[0010] During the immersion process, the ultrasonic time is 2 to 20 minutes and the stirring time is 10 to 40 minutes.
[0011] The process of preparing α-diisobutylene by catalyzing isobutylene with the catalyst of the present invention is as follows: laboratory small test kettle reaction, the conditions are: reaction pressure is normal pressure ~ 2MPa nitrogen protection pressure, reaction temperature is 70 ~ 90 ° C, reaction time is 2 ~ 5 hours, cooling and releasing gas after the reaction, collecting product analysis and calculation results.
[0012] Compared with the prior art, the present invention has the following beneficial effects: The catalyst preparation process is simple and the reaction conditions are mild: no pressure, low reaction temperature and low energy consumption; the selectivity of α-diisobutylene in the prepared product is high, and the selectivity of α-diisobutylene in the generated dimerization product diisobutylene is above 90%. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 These are SEM images of the Beta60 molecular sieve before (a) and after (b) loading metal in Example 3 of the present invention.
[0014] Figure 2 This is the XRD diagram of the Beta60 molecular sieve before and after metal loading in Example 3 of the present invention.
[0015] Figure 3This is the GC-MS spectrum of the synthesis of α-diisobutylene from isobutylene catalyzed by 7%Cu5%Co / Beta60 in Example 3 of the present invention. DETAILED DESCRIPTION
[0016] The technical solution will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, what is described is a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, professionals familiar with the art can clearly understand the technical advantages and performance effects of the present invention. All other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0017] After the catalyst was prepared, the reactor was cleaned with water before the isobutylene polymerization experiment was carried out, and then dried and cooled to a low temperature for use. Agilent gas chromatography-mass spectrometry was the main analytical instrument for this experiment.
[0018] Example 1 Weigh 1.70g of copper nitrate trihydrate and dissolve it in 3.40g of deionized water. After fully dissolving, add 4.01g of Beta60 molecular sieve, stir evenly, and stir for 30 minutes after ultrasonic treatment for 5 minutes. Dry in an oven at 80℃ for 2 hours and calcine in a muffle furnace at 500℃ for 3 hours to prepare a 10%Cu / Beta60 catalyst. Add 0.10g 10%Cu / Beta60 and 8.4g isobutylene to a frozen 90mL reactor, stir at 75℃ and 450 rpm, and react for 3 hours under 2MPa nitrogen pressure. After the reaction is completed, cool and degas, collect the product, and the calculated conversion rate is 59.5%. The results of gas chromatography-mass spectrometry analysis show that the total selectivity of diisobutylene is 53.8%, of which the selectivity of α-diisobutylene is 90.2%.
[0019] Example 2 Weigh 3.85g of copper nitrate trihydrate and dissolve it in 3.41g of deionized water, add 4.02g of Beta60 molecular sieve, stir evenly, ultrasonicate for 10 minutes and then stir for 20 minutes. Dry in an oven at 80℃ for 3 hours and calcine in a muffle furnace at 500℃ for 3 hours to prepare a 20%Cu / Beta60 catalyst. Add 0.09g of 20%Cu / Beta60 and 8.2g of isobutylene to a frozen 90mL reactor, stir at 80℃ and 500 rpm, react for 3 hours under 1MPa nitrogen pressure, cool and degas, collect the product, and calculate the conversion rate to be 55.8%. The results of gas chromatography-mass spectrometry analysis showed that the total selectivity of diisobutylene was 55.0%, of which the selectivity of α-diisobutylene was 90.5%.
[0020] In addition to preparing copper-modified Beta60 molecular sieve catalysts, we also prepared metal / Beta60 catalysts with different contents of other metals such as cobalt, nickel, and zinc. After using them for catalytic reactions, we found that the results were not always ideal. We considered whether it was because of the single metal modification that more α-diisobutylene (2,4,4-trimethyl-1-pentene) was generated during the isobutylene polymerization reaction instead of converting to another structure (2,4,4-trimethyl-2-pentene). Then, adding another metal, so that the two metals form a ligand structure, can achieve the experimental intention, so we prepared a bimetallic modified Beta60 molecular sieve catalyst. Through the interaction between the two metals as ligands and the molecular sieve, the highly selective preparation of α-diisobutylene during the isobutylene polymerization process can be achieved.
[0021] Example 3 Weigh 1.14g of copper nitrate trihydrate and 1.01g of cobalt nitrate hexahydrate and dissolve them in 3.40g of deionized water, add 4.01g of Beta60 molecular sieve, stir evenly, ultrasonicate for 10 minutes and then stir for 30 minutes. Dry in an oven at 80℃ for 3 hours and calcine in a muffle furnace at 500℃ for 3 hours to prepare a 7%Cu5%Co / Beta60 catalyst. Take a frozen 90mL reactor, add 0.09g of 7%Cu5%Co / Beta60, 8.2g of isobutylene, stir at 75℃, 500 rpm, and react at normal pressure for 3 hours. After the reaction is completed, cool and degas, collect the product and calculate the conversion rate to be 57.9%. The results of gas chromatography-mass spectrometry analysis show that the total selectivity of diisobutylene is 59.7%, of which the selectivity of α-diisobutylene is 91.3%.
[0022] The SEM images of the 7%Cu5%Co / Beta60 catalyst and the Beta60 carrier are shown in Figure 2. Figure 1 As shown in the figure, it can be seen that the surface microstructure of the catalyst modified by active metal copper and cobalt has a certain agglomeration phenomenon compared with the original carrier. This structural change causes the reactant isobutylene to be converted more to α-diisobutylene during the catalytic reaction, and to a certain extent prevents the formation of trimers.
[0023] The XRD patterns of the 7%Cu5%Co / Beta60 catalyst and the carrier Beta60 are shown in Figure 2. The two catalysts show characteristic diffraction peaks belonging to BETA molecular sieve at 2θ=7.8° and 22.4°, indicating that the catalyst is BETA molecular sieve. After adding the active metal component, the intensity of the two characteristic diffraction peaks of BETA molecular sieve decreased, indicating that the addition of the active metal component has an effect on the lattice strength of the BETA molecular sieve. In particular, the three peaks of the 7%Cu5%Co / Beta60 catalyst between 2θ=36°~40° indicate that the addition of the active metal component has caused certain changes in the lattice structure of the Beta60 molecular sieve.
[0024] The GC-MS spectrum of 7%Cu5%Co / Beta60 catalyst for synthesizing α-diisobutylene from isobutylene is shown in Figure 3 As shown, the peak appearing at the acquisition time of 2.314 min is α-diisobutylene, and the peak appearing at 2.485 min is the diisobutylene signal peak. The total selectivity is 59.7%, of which the α-diisobutylene selectivity accounts for 91.3%.
[0025] Example 4 Weigh 0.82g of copper nitrate trihydrate and 4.94g of cobalt nitrate hexahydrate and dissolve them in 3.40g of deionized water, add 4.01g of Beta60 molecular sieve, stir evenly, ultrasonicate for 5 minutes and then stir for 20 minutes. Dry in an oven at 80℃ for 3 hours and calcine in a muffle furnace at 500℃ for 3 hours to prepare a 5%Cu20%Co / Beta60 catalyst. Take a frozen 90mL reactor, add 0.11g of 5%Cu20%Co / Beta60, 8.6g of isobutylene, stir at 75℃, 500 rpm, and react at normal pressure for 3 hours. After the reaction is completed, cool and degas, collect the product and calculate the conversion rate to be 53.6%. The results of gas chromatography-mass spectrometry analysis show that the total selectivity of diisobutylene is 64.3%, of which the selectivity of α-diisobutylene is 91.8%.
[0026] Example 5 Weigh 0.99g nickel nitrate hexahydrate and 1.98g cobalt nitrate hexahydrate and dissolve them in 3.20g deionized water, add 4.02g Beta60 molecular sieve, stir evenly, ultrasonicate for 10 minutes and then stir for 30 minutes. Dry in an oven at 80℃ for 3 hours and calcine in a muffle furnace at 600℃ for 2.5 hours to prepare a 5%Ni10%Co / Beta60 catalyst. Take a frozen 90mL reactor, add 0.06g5%Ni10%Co / Beta60, 8.3g isobutylene, stir at 80℃, 500 rpm, and react at normal pressure for 3 hours. After the reaction is completed, cool and degas, collect the product and calculate the conversion rate to be 59.5%. The results of gas chromatography-mass spectrometry analysis show that the total selectivity of diisobutylene is 56.4%, of which the selectivity of α-diisobutylene is 88.6%.
[0027] Example 6 Weigh 0.57g of copper nitrate trihydrate and 0.49g of cobalt nitrate hexahydrate and dissolve them in 3.30g of deionized water, add 4.00g of Beta60 molecular sieve, stir evenly, ultrasonicate for 2 minutes and then stir for 20 minutes. Dry in an oven at 80℃ for 2.5 hours and calcine in a muffle furnace at 550℃ for 3 hours to prepare a 3.75%Cu2.5%Co / Beta60 catalyst. Take a frozen 90mL reactor, add 0.08g of 3.75%Cu2.5%Co / Beta60, 8.3g of isobutylene, stir at 85℃, 500 rpm, and react at normal pressure for 3 hours. After the reaction is completed, cool and degas, collect the product and calculate the conversion rate to be 56.3%. The results of gas chromatography-mass spectrometry analysis show that the total selectivity of diisobutylene is 58.5%, of which the selectivity of α-diisobutylene is 90.3%.
[0028] Example 7 Weigh 2.21g nickel nitrate trihydrate and 4.93g cobalt nitrate hexahydrate and dissolve them in 3.80g deionized water, add 4.01g Beta60 molecular sieve, stir evenly, ultrasonicate for 2 minutes and then stir for 20 minutes. Dry in an oven at 80℃ for 2.5 hours and calcine in a muffle furnace at 550℃ for 3 hours to prepare a 10%Ni20%Co / Beta60 catalyst. Take a frozen 90mL reactor, add 0.05g10%Ni20%Co / Beta60, 8.6g isobutylene, stir at 80℃, 500 rpm, and react at normal pressure for 3 hours. After the reaction is completed, cool and degas, collect the product and calculate the conversion rate to be 60.1%. The results of gas chromatography-mass spectrometry analysis show that the total selectivity of diisobutylene is 62.1%, of which the selectivity of α-diisobutylene is 90.1%.
[0029] Comparative Example 1 Take a frozen 90mL reactor, add 0.08g Beta60 molecular sieve, 8.3g isobutylene, 75℃, 500 rpm stirring, and react for 3 hours under 2MPa nitrogen pressure. After the reaction is completed, cool and degas, collect the product and calculate the conversion rate to be 46.5%. The results of gas chromatography-mass spectrometry analysis: the total selectivity of diisobutylene is 32.0%, of which the selectivity of α-diisobutylene is 80.6%. This comparative example is added when the catalyst screening is started. The Beta60 molecular sieve itself has catalytic activity for the reaction, but the reaction result is not very ideal. Through the loading modification of active metals, the current target requirements can be met at present.
[0030] Comparative Example 2 Weigh 1.11g of phosphotungstic acid and dissolve it in 0.9g of deionized water, add 1.01g of Beta60 molecular sieve, stir evenly, ultrasonicate for 2 minutes and then stir for 20 minutes. Dry in an oven at 100℃ for 2.5 hours and calcine in a muffle furnace at 300℃ for 3 hours to prepare a 20% phosphotungstic acid / Beta60 catalyst. Take a frozen 90mL reactor, add 0.06g of 20% phosphotungstic acid / Beta60, 8.3g of isobutylene, stir at 70℃, 500 rpm, and react for 3 hours under 2MPa nitrogen. After the reaction is completed, cool and degas, collect the product and calculate the conversion rate to be 86.5%, and the results of gas chromatography-mass spectrometry analysis show that the total selectivity of diisobutylene is 53.3%, of which the selectivity of α-diisobutylene is 71.1%. In this comparative example, the catalyst prepared by loading modified Beta60 molecular sieve with phosphotungstic acid has a higher conversion rate than the catalyst modified with metal copper, cobalt, etc., due to the strong acidity of phosphotungstic acid itself, but the selectivity of α-diisobutylene is much worse, and more trimers and even tetramers are produced, which fails to achieve the expected purpose.
[0031] The above is only a specific implementation example of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a catalyst for preparing α-diisobutylene by isobutylene oligomerization, characterized in that: Dissolve copper, cobalt or nickel nitrate in deionized water, add carrier Beta molecular sieve, impregnate with equal volume, ultrasonicate, stir, dry at 70-100° C., heat to 300-600° C. in a muffle furnace and calcine for 2-5 hours to obtain the catalyst for isobutylene polymerization.
2. A method for preparing a catalyst for preparing α-diisobutylene by isobutylene oligomerization as claimed in claim 1, characterized in that: The nitrate of copper, cobalt or nickel is one or more of copper nitrate trihydrate, cobalt nitrate hexahydrate and nickel nitrate hexahydrate.
3. A method for preparing a catalyst for preparing α-diisobutylene by isobutylene oligomerization as claimed in claim 1, characterized in that: The mass ratio of the copper, cobalt or nickel nitrate to the Beta molecular sieve is 1:5-1:
40.
4. A method for preparing a catalyst for preparing α-diisobutylene by isobutylene oligomerization as claimed in claim 1, characterized in that: During the immersion process, the ultrasonic time is 2 to 20 minutes and the stirring time is 10 to 40 minutes.
5. Use of the catalyst synthesized by the method as claimed in claim 1 in catalyzing the oligomerization of isobutylene to synthesize α-diisobutylene.
6. Use of the catalyst according to claim 5 in catalyzing the oligomerization of isobutylene to synthesize α-diisobutylene, characterized in that: The amount of the catalyst added is 0.5% to 1.5% of the amount of isobutylene added, and the reaction conditions are normal pressure to 2 MPa nitrogen protection pressure, temperature 70 to 90° C., and time 2 to 5 hours.